Systematic Literature Review of English Journal Articles on the Use of Artificial Intelligence Applications in English Academic Writing - Tanri Wulan, Dian; Syamsiarna Nappu; Saiful, Saiful (Universitas Cokroaminoto Palopo, 2025)
The integration of Artificial Intelligence (AI) in academic writing has gained increasing attention in recent years, offering innovative tools that assist in enhancing the quality and efficiency of English academic writing. This systematic literature review aims to explore the current landscape of AI applications in English academic writing by analyzing peer-reviewed journal articles published in English. The review focuses on identifying the key AI tools and the types of AI program employed, their contribution on academic writing, and the implications for students and educators. The study synthesizes findings from a comprehensive selection 108 of articles, highlighting trends in AI-assisted writing, such as grammar and paraphrasing. The review also describe the ethical considerations surrounding AI use in academia, including issues of academic integrity and plagiarism. By providing a detailed overview of existing research, this research contributes to the understanding of how AI is transforming English academic writing and offers insights for future researchand practical applications in educational settings.